Kedudukan Prinsip Imparsialitas atas Gugatan Vexatious dalam Penegakan Hukum pada Proses Mediasi - Anggriawan, Teddy Prima; Wardhani, Shinfani Kartika; Wibiantoro, Donny Yuhendra (UNES Law Review, 2023)
Impartiality is basically a principle that is applied to the mediation process, where the mediator is obliged to apply this principle without taking sides with either party. However, as development continues to progress, it is found that there are parties who actually litigate issues based on bad faith. This is usually called a vexational lawsuit, which is filed by a party with the sole aim of annoying the opposing party. Based on this, it is then worth exploring the position of the principle of impartiality by mediators in the mediation process when faced with filing a lawsuit which is indicated to be a vexatious lawsuit which could of course end up harming one of the parties. The type of research used is normative juridical. The approach is towards statutory regulations and legal concepts. The research results found that the principle of impartiality is a basic principle that must be applied by mediators in the mediation process. The indication that there is a vexatious claim does not actually constitute the mediator's authority to assess further to side with one of the parties. The mediator only focuses on reconciling the parties. The position of the principle of impartiality must therefore still be upheld, because it is a standard concept in civil law which is related to the realization of legal certainty.